Concise Guide to Software Engineering - O’Regan, Gerard (Springer, 2017)
The objective of this book was to provide a concise introduction to the software engineering field to students and practitioners. The principles of software engineering are discussed, and the goal is to give the reader a grasp of the fundamentals of the software engineering field, as well as guidance on how to apply the theory in an industrial environment.
From Fundamentals to Application Methods